Effect of Trichoderma sp. on Anthracnose Disease of Stored Chilli - Yan, Zee Kar; Tu Anh, Vu Thanh (Borneo Journal of Resource Science and Technology, 2018)
Chilli is commonly used as spice in Malaysian culinary, principal ingredients in paste (sambal) and as the raw material in sauce industry. Anthracnose disease caused by Colletotrichum capsici is one of the major causes of economic loss to chilli production especially in Asia. Even a small lesion on chilli might affect the quality, thus the market value of the chilli. Disease symptoms caused by C. capsici include brown, circular and sunken lesion with concentric rings of black acervuli. Chemicals have been used to treat the chilli but they might cause environmental pollution, affect human health and lead to pathogen resistance to the chemicals. Therefore, an alternative method to chemical control is required. In this study, C. capsici was isolated from a naturally infected chilli fruit (Capsicum frutescens), and a species of Trichoderma was isolated from the rhizosphere of grasses. Pure cultures of both fungi were established then used in antagonism studies in in vitro and in vivo. Dual culture of pathogens and Trichoderma sp. indicated that Trichoderma sp. competed with C. capsici for space and nutrients, caused the loss of turgidity of the fungal hyphae, and reduced the fungal growth by producing volatile metabolites. Trichoderma sp. decreased disease severity on chilli artificially inoculated fruits up to 64% when Trichoderma mycelial plug was used and 55% when culture filtrate was applied. Field trials are recommended to examine the antagonism of Trichoderma sp. in real production conditions. Keywords: Anthracnose, biological control, Colletotrichum capsici, Trichoderma sp.